MORTALITY OF PATIENTS HOSPITALIZED BY COVID-19 IN MEXICO, SYSTEMATIC REVIEW: MORTALIDAD DE PACIENTES HOSPITALIZADOS POR COVID-19 EN MÉXICO, REVISIÓN SISTEMÁTICA - Portocarrerero Granados , Ana (2024)
Introduction Since the start of the pandemic, Mexico was one of the countries with the highest mortality rates from COVID 19. Objective To determine if type 2 diabetes mellitus, arterial hypertension, and obesity increase mortality in patients diagnosed with COVID-19 who required hospitalization in Mexico. Method Systematic review in Pubmed MeSH, Web of Science, Lilas, Scielo, and Google Schoolar with the terms MESH COVID-19, SARS-COV2, Coronavirus, and Mexico for the years 2020 and 2021, in English or Spanish. Two reviewers selected the studies, two additional reviewers participated in the analysis of the studies. Results Seventy three studies carried out in Mexico from 2020 to 2021 were included with information obtained from the databases of the National Epidemiological Surveillance System of Mexico. With an average age of 52.9 ± 13.27 years, 64% of the included patients were women, the most prevalent pathology was obesity with 24.23% (IQR 17.74-22.28 = 22%), followed by hypertension. arterial 22.23% (IQR 17.98-23.44 = 22%) and finally Diabetes mellitus with 18.10% (interquartile range 9.39 -14.61 = 22%). In general, a mortality rate of 16.76 (IQR 9-39-14.61) was reported. 71% of the studies (52) did not report specific mortality related to comorbidities. conclusions The most common comorbidity among patients hospitalized for COVID in Mexico was obesity, followed by type 2 diabetes mellitus and hypertension.